Proceedings from the Inaugural American Initiative in Mast Cell Diseases (AIM) investigator conference - Gotlib, Jason; George, Tracy I.; Carter, Melody C.; Austen, K. Frank; Bochner, Bruce; Dwyer, Daniel F.; Lyons, Jonathan J.; Hamilton, Matthew J.; Butterfield, Joseph; Bonadonna, Patrizia; Weiler, Catherine; Galli, Stephen J.; et al. (The journal of allergy and clinical immunology, 2021)
The American Initiative in Mast Cell Diseases (AIM) held its inaugural investigator conference at Stanford University School of Medicine in May 2019. The overarching goal of this meeting was to establish a Pan-American organization of physicians and scientists with multidisciplinary expertise in mast cell disease. To serve this unmet need, AIM envisions a network where basic, translational, and clinical researchers could establish collaborations with both academia and biopharma to support the development of new diagnostic methods, enhanced understanding of the biology of mast cells in human health and disease, and the testing of novel therapies. In these AIM proceedings, we highlight selected topics relevant to mast cell biology and provide updates regarding the recently described hereditary alpha-tryptasemia. In addition, we discuss the evaluation and treatment of mast cell activation (syndromes), allergy and anaphylaxis in mast cell disorders, and the clinical and biologic heterogeneity of the more indolent forms of mastocytosis. Because mast cell disorders are relatively rare, AIM hopes to achieve a coordination of scientific efforts not only in the Americas but also in Europe by collaborating with the well-established European Competence Network on Mastocytosis.
Gesehen am 25.08.2021